2019
DOI: 10.1016/j.ijantimicag.2019.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic activity of colistin with azidothymidine against colistin-resistant Klebsiella pneumoniae clinical isolates collected from inpatients in Greek hospitals

Abstract: Background: New antibiotics are urgently needed for the treatment of multidrug resistant infections. However, the production of novel antibiotics is diminishing. The enhancement of activity of available antibiotics through synergistic combination drug therapy may help in the management of patients with resistant infections. Methods: Colistin-resistant Klebsiella pneumoniae isolates were collected from inpatients in 10 Greek hospitals and used in the study of combination activity of colistin plus azidothymidine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 28 publications
(33 reference statements)
2
14
0
Order By: Relevance
“…Subsequently, zidovudine has been demonstrated to have potent activity against many pathogenic Gram-negative bacteria, including Escherichia coli , Salmonella typhimurium , Klebsiella pneumoniae , Shigella flexneri, and Haemophilus influenzae and including isolates resistant to conventional antibiotics (Keith et al., 1989; Sandrini et al., 2007a,b; Doleans-Jordheim et al., 2011; Peyclit et al., 2018). It also acts synergistically with conventional antibiotics, enhancing their effectiveness (Wambaugh et al., 2017; Ng et al., 2018; Falagas et al., 2019; Hu et al., 2019). Zidovudine is ineffective against Gram-positive bacteria such as Listeria species, Bacillus species, Staphylococci, and Enterococcus faecalis as well as against Mycobacteria species and Pseudomonas aeruginosa (Elwell et al., 1987; Sandrini et al., 2007a).…”
Section: Pyrimidine Analoguesmentioning
confidence: 99%
“…Subsequently, zidovudine has been demonstrated to have potent activity against many pathogenic Gram-negative bacteria, including Escherichia coli , Salmonella typhimurium , Klebsiella pneumoniae , Shigella flexneri, and Haemophilus influenzae and including isolates resistant to conventional antibiotics (Keith et al., 1989; Sandrini et al., 2007a,b; Doleans-Jordheim et al., 2011; Peyclit et al., 2018). It also acts synergistically with conventional antibiotics, enhancing their effectiveness (Wambaugh et al., 2017; Ng et al., 2018; Falagas et al., 2019; Hu et al., 2019). Zidovudine is ineffective against Gram-positive bacteria such as Listeria species, Bacillus species, Staphylococci, and Enterococcus faecalis as well as against Mycobacteria species and Pseudomonas aeruginosa (Elwell et al., 1987; Sandrini et al., 2007a).…”
Section: Pyrimidine Analoguesmentioning
confidence: 99%
“…In addition to antivirus activity, several studies have demonstrated the in vitro antimicrobial properties of azidothymidine against Enterobacteriaceae including K. pneumoniae 39,40 . Meanwhile, azidothymidine has shown in vitro synergistic activity with colistin 41 or other small antimetabolite molecules such as floxuridine 42 against resistant Enterobacteriaceae clinical isolates. It has been indicated that azidothymidine acts as a DNA chain terminator owing to the substitution of 3-hydroxyl group in thymidine by an azide group, which thereby prevents the incorporation of DNA polymerases with the following nucleotide 43 .…”
Section: Discussionmentioning
confidence: 99%
“…While the mechanism of action may be directly related to the ability of colistin to allow other antimicrobials to penetrate the bacterial envelope, the inhibition of efflux pumps as a consequence of the membrane damage induced by colistin cannot be ruled out. In fact, there is increasing evidence that colistin can enhance the activities of a large number of antimicrobials [26,27] or enlarge their spectrum of action [28]. Funding: This research was funded by the Marató TV3 Foundation (BARNAPA project).…”
Section: Discussionmentioning
confidence: 99%